Hegelian motives in Thomas Mann’s “Joseph and his brothers” - Woźniak, Monika (Hybris, 2013)
The article discusses relations between Thomas Mann’s Joseph and his brothers and Hegelian conception of history and time. These two names are rather rarely linked together; in spite of Susan von Rohr Scaff’s works, the issue remains unexplored. I point out the similarities between Mann’s and Hegel’s understanding of eternity, the end of history and Absolute. Comparising their writings, I also refer to their cultural and historical background, suggesting that their common experience of modernity affects the tendency to synthesis that joins them.